A case study: to reduce process variability of valve seat depth in cylinder head using Six Sigma methodology. (2016) - Parsana, Tejaskumar S.; Desai, Darshak A.
The research has been carried out to introduce Six Sigma methodology in India, particularly in manufacturing SMEs. This paper deliberates the quality and productivity improvement in a cylinder head manufacturing enterprise through a case study and deals with an application of Six Sigma methodology in an industry which offers a framework to identify, quantify and abolish sources of variation in the manufacturing process of cylinder head, to optimise the operation variables, improve and endure performance viz. process yield through well-executed control plans. To support in the fulfilment of the purpose a practical DMAIC project was conducted. Six Sigma will provide a structure and training in tools, thereby ensuring that the tools are used at the right time and in the right way at the machining division. Application of Six Sigma methodology has resulted in enormous financial savings for the industry.